Analisis Keunggulan Komparatif Ekspor Lada Indonesia Tahun 2010 - 2016 - Repi Jusuf; Ni Putu Wiwin Setyari (INDEF - Institute for Development of Economics and Finance, 2020)
This study aims to determine the comparative advantage of Indonesian pepper commodity exports to its trading partner countries, Vietnam and Malaysia by using the Revealed Symmetric Comparative Advantage (RSCA) analysis method. In addition, this study aims to look at intra-industry trade between the three countries using the Intra-Industry Trade Index (IIT Index) analysis technique using data in period 2010 - 2016. Based on the results of testing using the RSCA method, Indonesian, Vietnam and Malaysia pepper commodity exports has comparative advantages in the ASEAN market in the period 2010-2016. Based on the results of testing using IIT analysis techniques, intra-industry trade between Indonesia and Vietnam and Malaysia is not dominant in similar commodities. Key words : Comparative Competitiveness, Pepper Commodity Export, Revealed Symmetric Comparative Advantage, Intra-Industry Trade